The diagnostic accuracy of EyeGuide Focus testing for concussion in elite male rugby players - Fuller, G. W.; Brown, J.; Dunlop, M.; Raftery, M.; Falvey, É. C. (The Physician and Sportsmedicine, 2025)
Introduction